Living Sharia: Law and Practice in Malaysia by Timothy P. Daniels - Shah, Shanon (Religions of South Asia, 2021)
Living Sharia: Law and Practice in Malaysia by Timothy P. Daniels. Seattle, WA: University of Washington Press, 2017. 280 pp., $30 (pb). ISBN 978-0-29574-255-7.